A whale of the wild - Parry, Rosanne (Greenwillow Books, an imprint of HarperCollins Publishers, 2021)
"For Vega and her family, salmon is life. And Vega is learning to be a salmon finder, preparing for the day when she will be her family's matriarch. But then she and her brother Deneb are separated from their pod when a devastating earthquake and tsunami render the seascape unrecognizable. Vega must use every skill she has to lead her brother back to their family. The young orcas face a shark attack, hunger, the deep ocean, and polluted waters on their journey. Will Vega become the leader she's destined to be?"--Amazon